Development and criterion validity of the COVID-19 anxiety and fear assessment scale: a cross sectional study - Gómez-Salgado, Juan; Allande-Cussó, Regina; Rodríguez-Domínguez, Carmen; Domínguez-Salas, Sara; Camacho-Martín, Selena; Romero-Ruiz, Adolfo; Ruiz-Frutos, Carlos (SAGE, 2021)
Background: The emergence of the new severe acute respiratory syndrome coronavirus 2, which causes COVID-19 disease, has been a major public health challenge and an increase in the feeling of uncertainty of the population, who is also experiencing an increase in levels of anxiety and fear regarding the COVID-19 disease. Objective: The objective of the study was the construct and criterion validation of the Escala de evaluación de la Ansiedad y MIedo a COVID-19 (AMICO, for its acronym in Spanish) to measure both constructs in the general Spanish population Methods: Descriptive study of psychometric validation. A field study was carried out to execute univariate and bivariate analyses, in addition to the exploratory and confirmatory factorial analysis of the scale. For the criteria validity study, the State-Trait Anxiety Inventory (STAI) and sensitivity and specificity values were calculated. Results: The study sample was composed of 1036 subjects over 18 years of age, who resided in Spain, where 56.3% were women with a mean age of 48.11 years (SD =15.13). The study of construct validity reported two factors and 16 items, with a Cronbach’s alpha value of 0.92. The scale was concurrently valid with the used gold standard and obtained sensitivity values of 90.48% and specificity values of 76%. Conclusions: The AMICO scale is valid and reliable for assessing the level of anxiety and fear of COVID-19 in the adult Spanish population and is highly sensitive.
Keywords: Ansiedad; Fear; Anxiety; COVID-19; Public health; Mental health; Instrument development